Zoom : pivoting to serve the surge of unexpected COVID-19 users (B) - Isaacs, Andrew M., (SAGE business cases., 2020)
In January 2020, the first case of COVID-19 was confirmed in the United States. American business leaders had heard the virus could cost the Chinese economy $60 billion that quarter, where the virus had a head start, but couldn't yet predict the economic impact in the U.S. Zoom Video Communications, Inc., headquartered in Silicon Valley, had some employees in China so it monitored the fast-moving virus and its potential financial and human impacts. The company knew it was in the eye of the storm.In its eight years, Zoom had managed rapid growth successfully in both the best and worst of times. It was a unicorn who took on existing industry players, both established and new. Yet at the end of February 2020, Santa Clara County Public Health, where Zoom was headquartered, announced the fourth case of COVID-19 and said it was preparing for community transmission. In its short history, Zoom had tackled four key challenges: inspiring a happy company culture during growth, outmaneuvering competitors, managing profitability and solving security problems. But did Zoom's past experience prepare the company to pivot, to withstand, and to perhaps even benefit from a looming outside, unexpected, global challenge of unknown proportions?